The physics and technology of diagnostic ultrasound : a practitioner's guide - Gill, Robert (Sydney, Australia : High Frequency Publishing, 2020)
An approachable textbook for medical practitioners and technologists who are studying to become ultrasound practitioners. Designed to suit the typical university, college or professional course of study. Also appropriate for those following a self-guided path to learning ultrasound.
1. Introduction -- 2. Ultrasound interaction with tissue -- 3. Pulsed ultrasound imaging -- 4. Transducers and focussing -- 5. Ultrasound instrumentation -- 6. Image artifacts -- 7. Doppler ultrasound -- 8. Doppler artifacts -- 9. Haemodynamic concepts -- 10. Imaging performance & limitations -- 11. Bioeffects and Safety -- 12. Additional modes and capabilities.
Online resource; title from digital title page (viewed on January 13, 2021).
Keywords: Diagnostic ultrasonic imaging; Ultrasonic imaging; Ultrasonography; Diagnostic ultrasonic imaging